Marzenie o szczęściu, czyli idea prawa natury w filozofi i Jana Jakuba Rousseau - Baranowska, Marta (Czasopismo Prawno-Historyczne, 2018)
In “Reveries of the Solitary Walker” Jean Jacques Rousseau described his idea of universal happiness as living a life in compliance with nature. However, as Rousseau noted, achieving that state of happiness was not at all easy, and fi rst the human nature needed to be understood. Looking at one’s life from the introspective point of view could be a useful tool, as well as looking a human person as the creation of God. According to Rousseau, the laws of nature derive from the human nature and should therefore govern the interpersonal relations among people. Consequently, since freedom and equality are the fundamental laws and each human being, people should always, by nature, treat each other as free and equal. This positive perception of a human being made Rousseau postulate that rather than follow authorities, individuals should have more confi dence and belief in themselves.